Anatomopathological characterization of placentas from HIV+ patients associated with p24 expression - López, Consuelo Lozoya; Pires, Andréa Rodrigues Cordovil; Fonseca, Eliene Carvalho De; Rodrigues, Fabiana Resende; Braga Neto, Antônio Rodrigues [UNESP]; Herdy, Gesmar Volga Haddad; Vasques, Flávio Augusto Prado; Lopes, Vania Gloria Silami (Sociedade Brasileira de Patologia ClínicaSociedade Brasileira de PatologiaSociedade Brasileira de Citopatologia, 2013)
INTRODUCTION: The study of placentas from pregnant human immunodeficiency virus (HIV) positive women has become the subject of numerous studies in the literature. Morphological, viral, immune and inflammatory placental aspects have been analyzed in order to grasp the vertical transmission of the virus. OBJECTIVE: To identify the most frequent findings in the placentas by associating them with a viral antigen and correlating them with the infection of newborns. MATERIAL AND METHODS: Thirty-five placentas from HIV- positive pregnant women were pathologically and immunohistochemically analyzed with the use of p24 antibody in the period from 1992 to1997 in accordance with the routine laboratory testing from the Anatomopathological Department - Hospital Universitário Antônio Pedro - Universidade Federal Fluminense (APD/HUAP/UFF). RESULTS: The microscopic alterations detected in all cases, including those with vertical transmission, were arteriopathy in the fetal blood circulation, chorioamnionitis, perivillous fibrin deposition, syncytial knotting, villous edema and villous immaturity. No specific macroscopic or histopathological changes were found in these placentas. The neonatal infection was observed in five cases. Vertical transmission was identified in two out of five placentas that had low weight for the respective stage of pregnancy. Immunohistochemical analysis revealed 14 positive cases, two of which showed vertical transmission. The viral protein was not identified in 10 out of 14 placentas from patients who had been medicated with zidovudine (AZT). CONCLUSION: Our study has contributed to the anatomopathological investigation into placentas from HIV-positive patients, although p24 expression per se did not allow a definite and early diagnosis of the vertical transmission.

INTRODUÇÃO: A importância do estudo da placenta de gestantes com o vírus da imunodeficiência humana (HIV) soropositivas tornou-se alvo de inúmeros trabalhos na literatura. Aspectos morfológicos, virais, imunes e inflamatórios intrínsecos ao tecido placentário foram analisados para o entendimento da transmissão vertical do vírus. OBJETIVO: Identificar as lesões mais frequentes nas placentas, associando-as ao antígeno viral e correlacionando-as com a infecção dos recém-nascidos. MATERIAL E MÉTODOS: Trinta e cinco placentas de gestantes HIV soropositivas foram analisadas por estudo anatomopatológico e imuno-histoquímico, utilizando o anticorpo p24, no período de 1992 a 1997, segundo a rotina do laboratório do Serviço Anatomia Patológica/Hospital Universitário Antônio Pedro/Universidade Federal Fluminense (SAP/HUAP/UFF). RESULTADOS: As alterações microscópicas registradas em todos os casos, inclusive nos de transmissão vertical, foram arteriopatia no circuito vascular fetal, corionamnionite, depósito fibrinoide perivilositário, excesso de nós sinciciais, edema do estroma viloso e dismaturidade vilosa. Nenhuma alteração microscópica ou macroscópica específica do HIV foi encontrada nas placentas. A infecção neonatal pôde ser constatada em cinco casos. A transmissão vertical foi identificada em duas placentas entre cinco que tinham baixo peso para a idade gestacional. Análise da imuno-histoquímica do p24 mostrou 14 casos positivos, dois dos quais apresentaram transmissão vertical. A proteína viral não foi identificada em 10 das 14 placentas cujas pacientes foram medicadas com zidovudina (AZT). CONCLUSÃO: Nosso estudo contribuiu para o estudo anatomopatológico da placenta de pacientes soropositivas para o HIV, porém a expressão do p24 por si só não permitiu um diagnóstico definitivo e precoce da transmissão vertical.
Caracterização anatomopatológica da placenta de pacientes HIV+ associada à expressão do p24
Keywords: placenta; exame anatomopatológico; HIV; imuno-histoquímica; p24; placenta; pathologic exam; HIV; immunohistochemistry; p24